2009
DOI: 10.1038/ejhg.2009.34
|View full text |Cite
|
Sign up to set email alerts
|

The role of sarcomere gene mutations in patients with idiopathic dilated cardiomyopathy

Abstract: We investigated a Danish cohort of 31 unrelated patients with idiopathic dilated cardiomyopathy (IDC), to assess the role that mutations in sarcomere protein genes play in IDC. Patients were genetically screened by capillary electrophoresis single strand conformation polymorphism and subsequently by bidirectional DNA sequencing of conformers in the coding regions of MYH7, MYBPC3, TPM1, ACTC, MYL2, MYL3, TNNT2, CSRP3 and TNNI3. Eight probands carried disease-associated genetic variants (26%). In MYH7, three nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 44 publications
1
54
1
Order By: Relevance
“…4,6,7,9,12,14,[22][23][24][25] In these patients 17 TNNT2 mutations have been found, of which six (35%) were the specific TNNT2 p.K217del mutation. Two studies only analysed exon 13 of the TNNT2 gene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,6,7,9,12,14,[22][23][24][25] In these patients 17 TNNT2 mutations have been found, of which six (35%) were the specific TNNT2 p.K217del mutation. Two studies only analysed exon 13 of the TNNT2 gene.…”
Section: Discussionmentioning
confidence: 99%
“…These mutations have been found in familial DCM in about 7%, 7% and 3% of index patients, respectively. [4][5][6]9,[12][13][14][15][16][17] Screening for mutations in genes coding for sarcomeric proteins is therefore considered useful in cases of both familial and non-familial DCM, when other causes for DCM are excluded.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The chance of carrying such an additional DCM-related mutation is believed to be o3%. 7,15,16 Index case in that family had not been tested: Idiopathic DCM is believed to be familial in about 30-50% of cases. Therefore, if an index patient has been clinically diagnosed with idiopathic DCM, and no genetic test has been performed, the chance for a first-degree relative to develop DCM may reach up to 15-25%.…”
Section: Negative Clinical Predictive Value (Probability Not To Develmentioning
confidence: 99%
“…11,12 Several studies have reported that DCM patients carrying more than one disease-associated mutation have an early onset, severe disease expression and a bad prognosis, which is most likely due to a gene-dosage effect. [13][14][15][16] It is expected that next-generation sequencing techniques will identify an increasing number of patients with such complex genotypes. Specificity:…”
Section: Diagnostic Settingmentioning
confidence: 99%